Flexible multi-tier dispute resolution in international tax disputes - Pistone, Pasquale 1968- (IBFD Publications USA, Incorporated, 2021)
This book is the first of its kind to abridge the whole phenomenon of cross-border tax disputes, from their prevention to their settlement.
Description based on publisher supplied metadata and other sources
Keywords: Tax evasion (International law); Taxation-Law and legislation; Electronic books